HUBUNGAN STATUS KESEHATAN DENGAN KEMATIAN JEMAAH HAJI EMBARKASI SOLO ANALISIS DATA SISKOHATKES TAHUN 2016 – 2018 (Fakultas Kedokteran Universitas Gadjah Mada, 2019)
Health status with the death of jemaah hajj embarkation Solo: siskohatkes data analysis in 2016-2018Purpose: This study aims to determine the relationship of health status, relationship between sex factors, level of education, occupation and distance of accommodation in Saudi Arabia with the death of HOC pilgrims for 2016-2018 Method: A case-control study without matching (unmatching) using secondary data from the Health Hajj Computerized Integrated Health Sector (Siskohatkes) Ministry of Health of the Republic of Indonesia. The population in this study was the HOC Embarkation pilgrims, when organizing Hajj in 2016-2018. The case group is the hajj pilgrims who died during the 2016-2018 pilgrimage that met the inclusion criteria. The control group is pilgrims who live until the end of the pilgrimage with a case-control ratio of 1: 1. Samples were taken by stratified random sampling method. Bivariable analysis using chi-square test, multivariable analysis using logistic regression test (logistic regression). Results: The health status of haj pilgrims is the most significant variable related to the death of HOC pilgrims Embarkation SOC in 2016-2018, in multivariable analysis, high-risk health status has a value of OR = 7.83 (p-value = 0.001, 95% CI = 2, 99 - 20.49). Other variables also related to the death of the pilgrims are gender (OR = 1.87, p-value = 0.003, 95% CI = 1.24 -2.84), education level (OR = 1.86, p-value = 0.004, 95 % CI = 1.22 - 2.84). Employment variables show protective results against the deaths of pilgrims (OR = 0.63, p-value = 0.039, 95% CI = 0.41 - 0.98). Conclusion: Death of Haj pilgrims Embarkation of SOC in 2016-2018 is related to health status, gender, education level and employment of pilgrims. The development of the health of pilgrims in the waiting period before departure needs to be increased in order to reduce the number of morbidity and mortality of pilgrims during the implementation of the pilgrimage.